Study of Community Knowledge on the Use of Medicinal Plants for Reproductive Health in Salemba Village - Wahyuni Alinengsih Wahyuni (Jurnal Life Birth, 2026)
Reproductive health is an important aspect of human health, encompassing physical, mental, and social conditions related to the reproductive system. The use of medicinal plants as traditional treatment is still widely practiced by the community, including for maintaining reproductive health. However, such practices are often not supported by adequate knowledge. This study aims to determine the level of community knowledge and analyze the relationship between respondent characteristics (age, education, and occupation) and the use of medicinal plants for reproductive health in Salemba Village.This study employed a quantitative analytic design with a cross-sectional approach. The sample consisted of 104 respondents selected using purposive sampling technique. Data were collected using a structured questionnaire that had been tested for validity and reliability. Data analysis was conducted using univariate and bivariate methods with the Chi-Square test.The results showed that the majority of respondents had a moderate level of knowledge (55.8%), followed by good (28.8%) and poor (15.4%). There was a significant relationship between age and knowledge (p = 0.041), education and knowledge (p = 0.002), and occupation and knowledge (p = 0.033). In addition, there was a significant relationship between the level of knowledge and the use of medicinal plants for reproductive health (p = 0.001). In conclusion, knowledge plays an important role in influencing the use of medicinal plants. Therefore, improving health education is necessary to promote the safe, effective, and rational use of medicinal plants. Keywords: knowledge, medicinal plants, reproductive health, community